Research progress in pathogenesis of diabetic kidney disease - ZHAO Xi; WU Jia-li; HUANG Zi-yue; LI Dong-yun; WEI Dan-xia (Linchuang shenzangbing zazhi)
Diabetic kidney disease(DKD) is a worldwide public health problem, which is the major cause for morbidity and mortality of patients with diabetes, and the main cause for end-stage kidney diseases. Because of the lack of effective treatment, the research on its mechanism has been the focus of clinical studies. The changes of renal hemodynamics, oxidative stress, inflammation and so on are all related to the pathogenesis of DKD, and the related studies point out that metabolic memory and epigenetics play an important role in the progression of DKD. In this review, we will summarize the progress of the pathogenesis of diabetic kidney disease in combination with the latest studies